Template for Continental Drifts (Simbiótica. Revista Eletrônica, 2022)
Photographic record of a work of art done in 2022, situated between installation and sculpture. Materials: Himalayan salt, water bowl, bench and plumb bob. Dimensions: 45 x 255 cm. The photographs are by Lucas Cuiabao and the author.Sculpt maps of the continents using pink Himalayan rock salt;Place a water bowl on a bench with a plumb bob marking the central point and lay out salt block-maps in bowl to create Pangea arrangement;Add water to bowl and execute movements to cause blocks to be displaced;Wait for salt to dilute and sediment in bottom of bowl;Watch as new world map design forms.